Landscape in the gallbladder mycobiome and bacteriome of patients undergoing cholelithiasis with chronic cholecystitis - Hu, Junqing; Tang, Jichao; Zhang, Xinpeng; Yang, Kaijin; Zhong, Ayan; Yang, Qin; Liu, Yanjun; Li, Yi; Zhang, Tongtong (Frontiers in Microbiology, 2023)
Gallstone disease (GSD) is associated with changes in the gut and gallbladder bacterial composition, but there is limited information on the role of the fungal community (mycobiome) in disease development. This study aimed to characterize the gallbladder mycobiome profiles and their interactions with bacteriome in GSD. A total of 136 bile and gallstone samples (34 paired for bacteriome and 33 paired for mycobiome) were obtained from calculi patients with chronic cholecystitis. Bile and gallstone bacteriome and mycobiome were profiled by 16S and internal transcribed spacer (ITS) rRNA gene sequencing. Gallbladder bacteriome, mycobiome, and interkingdom and intrakingdom interactions were compared between bile and gallstone. In general, microbial diversity was higher in bile than in gallstone, and distinct microbial community structures were observed among them. Deep Sea Euryarchaeotic Group, Rhodobacteraceae, and Rhodobacterales were microbial biomarkers of bile, while Clostridiales and Eubacterium coprostanoligenes were biomarkers of gallstone. Five fungal taxa, including Colletotrichum, Colletotrichum sublineola, and Epicoccum, were enriched in gallstone. Further ecologic analyses revealed that intensive transkingdom correlations between fungi and bacteria and intrakingdom correlations within them observed in gallstone were significantly decreased in bile. Large and complex fungal communities inhabit the gallbladder of patients with GSD. Gallstone, compared with bile, is characterized by significantly altered bacterial taxonomic composition and strengthens bacterial–bacterial, fungal–fungal, and bacterial–fungal correlations in the gallbladder of patients with GSD.